THE ASSESSMENT AND REPAIR OF THE PRECAST RC STRUCTURE EXPOSED TO FIRE - Radonjanin, Vlastimir; Malešev, Mirjana; Lukić, Ivan; Šupić, Slobodan; Vukoslavčević, Suzana (Journal of Applied Engineering Science, 2016)
This paper presents the assessment and repair of precast RC structure exposed to fire in Novi Sad. Detailed visual inspection, which includes described and classified damages and defects of  RC columns and beams, is presented in the paper. Control design of the built-in concrete and reinforcement, as well as geodetic survey and conclusion on the state of the structure, are carried out. Two possible repair solutions were analysed.
Keywords: repair; control design; visual inspection; fire; RC structure